Assessment of oral cavity condition at patients representing healthy and unhealthy lifestyle - Podsiadła-Urban, Gabriela; Cieszko-Buk, Maria; Bachanek, Teresa (Polish Journal of Public Health, 2012)
Introduction. In general perspective, lifestyle refers to a set of behavior patterns specific for particular individual, which can change depending on the social-environmental context. Also, lifestyle may be of large importance in promotion of health as well as preventing and curing illnesses. Aim. The aim of this study was to assess oral cavity condition at patients representing pro healthy and unhealthy lifestyle. Material and methods. The study included group of 177 patients. Interview was conducted by means of anonymous questionnaire regarding one’s lifestyle and health-related behaviour as well as physical examination allowing the assessment of the condition of teeth, paradentium and the level of dental hygiene. Questions concerning lifestyle were drawn up based on the questionnaire created by American Public Health Service. According to given answers, a health profile of every patient was formed qualifying the individual to one of the three groups of behvior pattern: healthy, unhealthy or intermediate. Results. The analysis of health habits test of the examined demonstrated that 32.20% (n= 57) of patients represented healthy lifestyle, 13.56% (n=24) preferred extremly anti-healthy lifestyle. The most of the examined (n=96; 54.24%) represented moderate health care. Average PUW number in pro-healthy lifestyle group was 16.59 and was lower than average PUW numbers in other groups (17.48 at the group with anti-healthy behavior patterns, and 17.19 at the group with intermediate health behavior pattern). Conclusions. It has been stated that preferences concerning lifestyle are significantly dependent on the age, sex and material status, and to a lesser degree on the education, and aren’t dependent on the occupational activity. The most beneficial parameters of the clinical research were stated at patients with pro-healthy lifestyle; however important differences weren’t demonstrated between medical condition of the oral cavity at individuals demonstrating negative or intermediate health-related behaviours.